Implementation of environmental policy in the Republic of Uzbekistan - Saburova Juldizxan Axmetovna (Genius Publishing Group, 2022)
The article highlights the environmental problems left over from the times of the former Soviet Union before the independence of the Republic of Uzbekistan, the reforms carried out during the years of independence to solve them, as well as the facts that the reforms carried out in Uzbekistan to solve environmental problems were carried out on the basis of world experience.
Keywords: Ecology; Island disaster; environmental safety; environment